Safety climates in construction industry: understanding the role of construction sites and workgroups - Silva, S. (2013)
Studies of safety climate in construction revealed a significant positive association between safety climate and various aspects of occupational health and safety. The mechanisms through which this impact operates are still unclear and safety climate is usually studied without considering the complexity of this industry (companies, worksites and groups). The aim of this research is to analyze to what extend there are differences between construction sites and to explore the relations between construction sites’ safety climate and workers’ safety response and to examine how this influence occur considering the workgroups. The safety climate was evaluated using a reduced version of the questionnaire that is a part of Battery HERC (Herramienta para evaluacion riesgos comportamentales). The data were collected in a Portuguese construction company (5 construction sites; including sub-contractors) comprising 213 workers. Differences between construction sites safety climate were found, suggesting the prevalence of safety sub-climates. The workgroup safety climate played a determinant role on workers’ safety response in subcontracted workgroups and it is an important mechanism through which the principal contractor can influence subcontractors’ safety response. Designers of preven- tion and training programs for accidents prevention should include specific contents in order to improve supervisory safety leadership and workgroup safety responses.